Identify the differences between ordinary and barred spiral galaxies, NGC 2649 and NGC 4662 for examples - Ahmed, Abdulla K.; Taha, Anas S.; Kadhem, Arshed A. (Iraqi Journal of Science, 2024)
Since the beginning of mankind, the view of the sky was present through observations with the naked eye, then it developed with time, and the sciences and tools of astronomical observations developed, including photometric measurements, which reached a high degree of accuracy in describing various cosmic phenomena, including the study of galaxies, their composition, and the differences between them, and from here the importance of this study emerged, to determine the differences between two distinct types of classification of galaxies, which are normal and barred spiral galaxies, where two galaxies NGC 4662 and NGC 2649 were chosen that represented certain types of galaxies to study the morphological structure of the two galaxies, as well as the photometric study of the composition of the two galaxies, where a contour map was drawn, as well as finding the values of the photometric variables of the two galaxies, including the position angle, the ellipticity and B4. A fitting was made for the two galaxies to show the fundamental difference in composition, through which the basic differences between two known types of galaxies could be identified.